High Yield Electrosynthesis of Hydrogen Peroxide from Water Using Electrospun CaSnO3@Carbon Fiber Membrane Catalysts with Abundant Oxygen Vacancy. (17th April 2021) - Zhang, Chaoqi; Lu, Ruihu; Liu, Chao; Yuan, Ling; Wang, Jing; Zhao, Yan; Yu, Chengzhong
Abstract: Hydrogen peroxide (H2 O2 ) production by electrochemical two‐electron water oxidation reaction (2e‐WOR) is a promising approach, where high‐performance electrocatalysts play critical roles. Here, the synthesis of nanostructured CaSnO3 confined in conductive carbon fiber membrane with abundant oxygen vacancy (OV ) as a new generation of 2e‐WOR electrocatalyst is reported. The CaSnO3 @carbon fiber membrane can be directly used as a self‐standing electrode, exhibiting a record‐high H2 O2 production rate of 39.8 µmol cm −2  min −1 and a selectivity of ≈90% (at 2.9 V vs reversible hydrogen electrode). The CaSnO3 @carbon fiber membrane design improves not only the electrical conductivity and stability of catalysts but also the inherent activity of CaSnO3 . Density functional theory calculation further indicates the crucial role of OV in increasing the adsorption free energy toward oxygen intermediates associated with the competitive four‐electron water oxidation reaction pathway, thus enhancing the activity and selectivity of 2e‐WOR. The findings pave a new avenue to the rational design of electrocatalysts for H2 O2 production from water. Abstract : Nanostructured calcium stannate confined in conductive carbon fiber membrane with abundant oxygen vacancy is synthesized via electrospinning as a new generation of electrocatalyst for the two‐electron water oxidation reaction. When directly used as self‐standing electrodes, the hybrid material exhibits remarkable performances with high selectivity and production rate for hydrogen peroxide generation.